Efeito moderador do senso de coerência na relação entre percepção de discriminação racial e qualidade de vida relacionada à saúde bucal de escolares - Noronha, Thaís Gioda (2021)
Racial discrimination can act as a psychosocial stressor that underlies racial inequalities in oral health. Perception of discriminatory events can start in childhood and reflect in adolescence and adulthood and, through different social deprivations, can influence the individuals´ quality of life. The oral health-related quality of life (OHRQoL) refers to how much oral health conditions interfere with people´s daily life and well-being. Many epidemiological studies have evaluated the clinical, socioeconomic, social and environmental determinants that could possibly improve the oral health of individuals and populations, and among these determinants is the sense of coherence (SOC). The SOC is used to explain why some people continue to do well despite the stressful situations they face. Thus, considering that racial discrimination brings on stressful situations that impact on oral health perception, the aim of this study was to evaluate the moderating effect of SOC on the relationship between racial discrimination and OHRQoL in schoolchildren. This is a cross-sectional study nested in a cohort with 10 years of follow-up. OHRQoL was assessed using the reduced Brazilian version of the Child Perception Questionnaire (CPQ11-14). Perceived racial discrimination was assessed using a question contained in the Olweus Bullying Questionnaire – Victim, and to measure the sense of coherence, students answered the reduced version of the 13-item Sense of Coherence Scale (SOC-13). Data related to sex, age, skin color and socioeconomic conditions were also assessed. Poisson regression analysis was performed to test the moderating effect of SOC on the relationship between racial discrimination and OHRQoL. A total of 429 students were considered in this study. Considering the predictor variables separately, individuals who perceived racial discrimination had worse OHRQoL (RR 1.38; 95%CI 1.25-1.52); and individuals with higher SOC had better OHRQoL (RR 0.54 95%CI 0.51-0.57) than their counterparts. In the adjusted model, considering the interaction among racial discrimination and SOC, students who perceived racial discrimination, but had high SOC, reported less impact on OHRQoL (RR 0.70; 95% CI 0.55-0.89) than those with low SDC. Thus, the SOC can be considered a moderating variable in the relationship between racial discrimination and OHRQoL. These results highlight the potential importance of SOC in reducing the harmful effects of racial discrimination on OHRQoL.